Recurrent vaginal vault prolapse after vaginal hysterectomy with anterior-posterior mesh augmentation: a case report - Kreaingsak Sirisakpanich; Tsia-Shu Lo; Pei-Ying Wu (The Royal Thai College of Obstetricians and Gynaecologists, 2015)
Recurrent pelvic organ prolapse (POP) after transvaginal hysterectomy with mesh interposition and reinforcement has increased due to the widespread use of polypropylene mesh. We report a case of recurrent POP 3 years after a transvaginal mesh repair. A 74-year-old multiparous woman with a body mass index of 29.6 kg/m2 presented with recurrent symptomatic of POP associated with urinary incontinence following polypropylene mesh augmentation. A thorough examination revealed mesh displacement and enterocele. Surgical correction included repositioning of the anterior and posterior mesh, McCall culdoplasty, unilateral sacrospinous ligament fixation and excision of the exposed mesh. This patient had an excellent short-term outcome; however, long-term follow up is required. In summary, the management of recurrent POP following transvaginal mesh is challenging and should be individualized.